Love tragedies in arabic and chinese literature - Aierken, Ailifeire (2020)
Every nation has its own example of love that has attracted much attention. Majnun Layla and Liang Shanbo and Zhu Yingtai are two well-known love tragedies in Arabic and Chinese literature. These two literary works share some similarities, but due to their different cultural backgrounds and different bringing-up environments, there also exist many differences. This study attempts to make a comparison between these two love tragedies. It is worth noting that these two celebrated literary works share some tragic elements but different in tragic nature. The study seeks to achieve the following objective: to summarize and distinguish the similarities and differences between the two plays in theme, character and plot. The method used in this study is textual analysis and comparative approach. The findings of this study are in the form of similarities and differences. Concerning the theme of the two plays, both plays eulogize love, praise female characters good nature and both pairs of lovers sacrificed for their love. However, the difference is the male protagonist sacrificed more than the female protagonist in Majnun Layla. In contrast, in Liang Shanbo and Zhu Yingtai the female protagonist sacrificed more than the male protagonist. Concerning the character，the protagonists in Majnun Layla show a bit more initiative than Liang Shanbo and Zhu Yingtai in expressing and defending love. In the aspect of plot structure, the similarity is the plot structure of the two plays share similar development of love. However, Majnun Layla's difference ends up with tragic denouement, while Liang Shanbo and Zhu Yingtai ends up with reunion denouement. The significance of such a kind of comparative study is that it will enhance our understanding of tragedies from different countries and practically help improve communication between different cultures.